BETWEEN LIVE AND LIFE: EXPLORING THE ONLINE PRESENCE OF PERFORMANCE ARTISTS - Gemini, Laura; Brilli, Stefano (AoIR Selected Papers of Internet Research, 2020)
In the last decade, the use of social media in the theatre scene has fueled debates on the possibility to redefine the performer-audience relationship on a wide scale. Scarce attention, however, has been paid on empirically studying how performance artists balance their use of social media between the need to promote their work and the ambition to experiment creatively on the medium affordances. This paper explores the use of social media by Italian contemporary theatre artists and companies. The study aims to explore the relational labour (Baym 2018) of performance artists in tracing the boundaries between online/offline performativity and between personal self-narration and artistic promotion. Through a combination of profile analysis and in-depth interviews, we want to understand how this artistic scene - that always experimented on intermedial and participatory possibilities - is making sense of social media. Preliminary results show how social media interaction and content production is becoming an integrated part of companies working routines. Companies position their social media activity outside a purely promotional logic. This anti-promotional ethos translates to a lack of efficacy in terms of strategic communication. However, it also lays the basis for the use of social media to expand performative practices. Although the interviewed companies do not exclude such a possibility, they lament their current inability in making such an attempt. Lacking resources is the most quoted explanation of this failure, followed by the refusal to compromise with the constraints of online languages, and the distrust of social media to reach wider audiences.